(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
This paper proposes to analyze the influence of the installation of photovoltaic systems in the power system network. In conventional power system network contains a synchronous generator to generate real and reactive power and it is located far away from the load center due to availability of raw material and water etc. This long distance transmission of power leads to losses in the system and it can be reduced by placing the power generation system nearer to the load center. The development of renewable sources of energy like wind power generation system and photovoltaic power generation will play vital role in this direction of loss minimization of the power system network. In modern power system, the installation the renewable sources of energy are very much essential to avoid the contamination of environment and to meet the future increasing electrical power demand. Hence, it is important to analyze the benefits of photovoltaic systems for the minimization loss of power in the power system. Here, WSSC 9-bus system is considered to analyze the impact of the proposed scheme.